2015
DOI: 10.1007/s00330-015-3839-4
|View full text |Cite
|
Sign up to set email alerts
|

Partial splenic embolization for thrombocytopenia in liver cirrhosis: predictive factors for platelet increment and risk factors for major complications

Abstract: • The platelet increment after PSE greatly depends on the splenic infarction ratio. • The non-infarcted splenic volume significantly affects the efficacy of PSE. • A high cholinesterase level contributes to the improvement of thrombocytopenia after PSE. • The non-infarcted splenic volume significantly affects the relapse of hypersplenism. • Complications are significantly associated with the infarcted splenic volume and Child-Pugh score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 21 publications
0
28
0
1
Order By: Relevance
“…Even though it revealed its value, it took a while for splenic embolization to get more accepted due to an elevated rate of adverse events, mainly spleen abscess formation, sepsis, spleen disruption, pancreas inflammation due to nontarget embolization and severe pulmonary infection . Recent literature, however, has demonstrated significant reduction in complication and mortality rates resulting from various reasons including improvements in the available materials for transcatheter embolization and angiography equipment, added to the changes in the PSE procedure, learned throughout the past 20 years .…”
Section: Introductionmentioning
confidence: 99%
“…Even though it revealed its value, it took a while for splenic embolization to get more accepted due to an elevated rate of adverse events, mainly spleen abscess formation, sepsis, spleen disruption, pancreas inflammation due to nontarget embolization and severe pulmonary infection . Recent literature, however, has demonstrated significant reduction in complication and mortality rates resulting from various reasons including improvements in the available materials for transcatheter embolization and angiography equipment, added to the changes in the PSE procedure, learned throughout the past 20 years .…”
Section: Introductionmentioning
confidence: 99%
“…Yamamoto et al reported that they could perform the treatment of HCC safely for patients who received splenectomy, and this contributed to prolonged OS in patients who underwent splenectomy compared with those who did not undergo splenectomy [31]. Although partial splenic embolization is another effective modality that is less invasive in patients with hypersplenism, some investigators have reported disadvantages such as high recurrence rates of thrombocytopenia and the possibility of infectious complications [32][33][34]. The Sp ?…”
Section: Discussionmentioning
confidence: 99%
“…Cai с соавт. (2016) исследовали прогностические факторы послеоперационного увеличения уровня тромбоцитов и факторы риска серьезных послеоперационных осложнений [15]. Выяснилось, что эффективность прироста тромбоцитов в значительной степени зависит от соотношения объемов зоны инфаркта и остальной части селезенки.…”
Section: современное состояние проблемыunclassified